2005
DOI: 10.1079/pgr200589
|View full text |Cite
|
Sign up to set email alerts
|

Associations between geographical origin and morphological characters in bread wheat (Triticum aestivum L.)

Abstract: We report the morphological typing of 13,337 accessions of bread wheat. The individual characters assessed were: awnedness, awn colour, glume colour, presence/absence of glume hairs, spike type, spike density, spike branching, grain colour, stem type (hollow/solid) and presence/absence of ligules. We have associated these morphological data with accession provenance, to analyse global patterns of the traits. Whereas some of the traits (awnedness, awn colour, glume colour, presence/absence of hairs on glumes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
1
17
0
6
Order By: Relevance
“…Purple pigments protect plant tissues from UV irradiation and are implicated in tolerance to drought, heavy metals, herbivores and pathogens (Gould 2004). Wheat varieties having red glumes (Rg) are frequent in growing regions characterized by high light intensity, a short growing season, and low temperatures during the vegetative period (Flaksberger 1935;Börner et al 2005;Martynov and Dobrotvorskaya 1997). …”
Section: Introductionmentioning
confidence: 99%
“…Purple pigments protect plant tissues from UV irradiation and are implicated in tolerance to drought, heavy metals, herbivores and pathogens (Gould 2004). Wheat varieties having red glumes (Rg) are frequent in growing regions characterized by high light intensity, a short growing season, and low temperatures during the vegetative period (Flaksberger 1935;Börner et al 2005;Martynov and Dobrotvorskaya 1997). …”
Section: Introductionmentioning
confidence: 99%
“…The requirement of phenotypic germplasm characterization in genebanks has been emphasized frequently (Lehmann and Mansfeld 1957;Engels and Visser 2003). Morphological characters have not only been used for formal taxonomical overviews of large germplasm collections, but also for studying geographical patterns in variation of large genebank collections of durum wheat (Jain et al 1975;Yang et al 1991), bread wheat (Börner et al 2005), barley (Tolbert et al 1979) and triticale (Furman et al 1997). For oat, a comparative study is missing, although efforts in gaining an overview based on molecular studies have been made (Fu et al 2003(Fu et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Different rotational and cultivation practices used by farmers in different parts of the archipelago might have contributed to the development of wheat landraces well adapted to local conditions. It has been demonstrated that geographical isolation of wheat at locations characterized by different environmental conditions acted as a source of crop diversification in relatively short time periods (Zeven 1998;Börner et al 2005;Bardsley and Thomas 2005). We hypothesize that the diversity of edapho-ecological conditions and agricultural practices present on Madeira promoted the development of the local wheat landraces.…”
Section: Discussionmentioning
confidence: 89%
“…However, high levels of atmospheric humidity on Madeira and ample precipitation would possibly favour the development of awnedness landraces. Therefore, we incline to claim that predominance of awned varieties on the island could be only explained by the initial place of provenance of these wheats (Vieira 1983a, b;Börner et al 2005).…”
Section: Discussionmentioning
confidence: 99%